2006
DOI: 10.1007/s11746-006-1215-x
|View full text |Cite
|
Sign up to set email alerts
|

Pheophytin α degradation products as useful indices in the quality control of virgin olive oil

Abstract: In previous studies we reported the presence of compounds with spectral characteristics similar to pheophytin α (Pheo α), which often accompany the Pheo α peak in the chromatographic profile of virgin olive oils (VOO) at 410 nm under normal-phase HPLC conditions. The occurrence and levels of these compounds were found to be affected by storage conditions of the oil samples. In the present study we investigated whether the major Pheo a degradation products, identified as pyropheophytin α (coeluting with the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…In accordance with our results, other investigators [5,30,37] found that PV of oils bottled in glass and PET stored at room temperature fluctuated during storage time and did not exceed the official limit during six months of storage. In the other hand, a linear increase in PV with storage time at room temperature in oil stored in glass bottles [9,10] and in tin plates [38] was reported. In the same line with our results in oil stored in glass, PET, and cans at room temperature and elevated temperature, PV decreased significantly with increasing storage time [7].…”
Section: Peroxide Valuementioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with our results, other investigators [5,30,37] found that PV of oils bottled in glass and PET stored at room temperature fluctuated during storage time and did not exceed the official limit during six months of storage. In the other hand, a linear increase in PV with storage time at room temperature in oil stored in glass bottles [9,10] and in tin plates [38] was reported. In the same line with our results in oil stored in glass, PET, and cans at room temperature and elevated temperature, PV decreased significantly with increasing storage time [7].…”
Section: Peroxide Valuementioning
confidence: 99%
“…Some reporters [30] found that total phenols of oils bottled in glass and PET container didn't show significant decrease during storage, while others reported an increase in phenolic compounds contents with increasing time of storage [10,28], a situation found in our findings when oil was stored in glass and cans after 180 days of storage compared to the previous sampling date (135 days), which could be due to hydrolysis of secoiridoid derivatives in oil. As phenolic compounds act as natural antioxidants in oil and inhibit autoxidation of lipids (RH) by trapping intermediate peroxyl radicals [48], their reduction during storage is a result of oil oxidation [38].…”
Section: Total Phenolic Compoundsmentioning
confidence: 99%
“…EVOO's definition originates from its first-class qualities. In the last few years, several techniques have been used for the quality control of EVOO, such as near-, mid- and Fourier-transform infrared spectroscopy [4,5], nuclear magnetic resonance spectroscopy [6], high-performance liquid chromatography–mass spectrometry [7], electro- and sonic-spray ionization mass spectrometry [8], capillary electrophoresis or electrochromatography [9], UV–visible spectroscopy [10] and high-resolution mass spectrometry [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…One particular class of compounds are those derived from the degradation of chlorophyll pigments, pheophytins (PP) and pyropheophytin (PPP) (Fig. ) .…”
Section: Introductionmentioning
confidence: 99%
“…Its level increases over time depending on the storage condition and if the oil is exposed to heat treatments during the refining process, such as deodorization . Therefore, this conversion is used as a sensitive indicator of stress during the manufacturing and storage of the oil .…”
Section: Introductionmentioning
confidence: 99%